The Evidence Base for Effectiveness of Preparedness Training: A Retrospective Analysis - Potter, Margaret A. (Association of Schools of Public Health, 2010)
OBJECTIVE: In 2007, the Centers for Disease Control and Prevention (CDC) commissioned an Evidence-Based Gaps Collaboration Group to consider whether past experience could help guide future efforts to educate and train public health workers in responding to emergencies and disasters. METHODS: The Group searched the peer-reviewed literature for preparedness training articles meeting three criteria: publication during the period when CDC's Centers for Public Health Preparedness were fully operational, content relevant to emergency response operations, and content particular to the emergency response roles of public health professionals. Articles underwent both quantitative and qualitative analyses. RESULTS: The search identified 163 articles covering the topics of leadership and command structure (18.4%), information and communications (14.1%), organizational systems (78.5%), and others (23.9%). The number of reports was substantial, but their usefulness for trainers and educators was rated only “fair” to “good.” Thematic analysis of 137 articles found that organizational topics far outnumbered leadership, command structure, and communications topics. Disconnects among critical participants—including trainers, policy makers, and public health agencies—were noted. Generalizable evaluations were rare. CONCLUSIONS: Reviews of progress in preparedness training for the public health workforce should be repeated in the future. Governmental investment in training for preparedness should continue. Future training programs should be grounded in policy and practice needs, and evaluations should be based on performance improvement.